Knowledge, attitude and practices regarding blood donation among rural population - A cross sectional study. - Verma, Shashi (2012)
ABSTRACT: Introduction: Blood is universally recognized as the most precious element that sustains life. It saves innumerable lives across the world in a variety of conditions. The need for blood is great - on any given day, approximately 39,000 units of Red Blood Cells are needed. More than 29 million units of blood components are transfused every year. Objective of the study: 1. To assess the Knowledge, Attitude and Practices regarding blood donation among rural population. Material and Method: This cross sectional study was conducted in Kakati-A sub centre, under Primary Health Centre Vantamuri of Belgaum district. The sample size was calculated using the formula n = 4pq/ d2 .The total sample needed for the study was 400. Data collection was done using pre-designed and pre-tested questionnaire. Results: Out of 400 study participants, the mean age was 29.92 ± 6.85 years and 278 (69.50%) were male and 122 (30.50%) were female. Most (71.00%) of the study participants belonged to Hindu religion and majority (75.50%) were living in nuclear type of family. It was noted that 95.56% male and 82.78% female participants were literates. In this study, 20.25% male participants were factory worker and 22.75% female participants were housewives. The present study also revealed that 44.00% and 35.25% of study participants belonged to socio-economic classes IV and V respectively, while only 0.25% belonged to class I. Among 400 study population, 258 (64.50%) were aware about blood group, only 40 (10%) knew their haemoglobin and majority 385 (96.25%) of them knew that blood can be donated to other person. Out of 373 participants who had knowledge about place for blood donation, 90 (24.12%) knew a single place, 128 (34.31%) knew two places and 155 (41.55%) knew more than two places for blood donation. Out of 400, 28 (7.00%) responded that minimum age to donate blood is 17-35 years. Similarly, 257 (64.25%) and 11 (2.75%) responded 17-45 years and 17-60 years respectively. With regards to donor's weight, 27 (6.75%), 203 (50.75%) and 9 (2.25%) responded that minimum weight to donate blood is 50 kg, 51 - 60 kg and above 70 kg respectively. Out of 137 who responded, 44 (11.00%) said that minimum interval to donate blood is 3 months, 68 (17.00%) 6 months and 25 (l6.25%) 12 months respectively. 261 (65.25%) participants told that the amount of blood drawn in each donation is less than 500 ml and 6 (1.50%) 500 -1000 ml. In our study, 222 (55.50%) respondents were aware that some investigations are done on the donated blood, 230 (57.50%) knew that blood in the blood bank is safe for blood transfusion, 229 (57.25%) believed that all surgical procedures whether minor or major require blood transfusion and 84 (21.00%) correctly had the knowledge that blood supply to the blood bank is less than required. The common source of information regarding blood donation was through mass communication (television, radio and news paper) 805 (69.13%). Among 324 study participants who had not donated blood, the two main reasons for not donating blood were not being approached 163(26.85%) lack of information 163 (26.85%). Majority 231 (46.02%) of study participants had no idea regarding effect of blood donation on one's health, whereas 108 (21.51%) responded that blood donation does not have any beneficial effect on the health and 37 (7.37%) thought that blood donation had a harmful effect on one's health. Out of 400 study participants, 300 (60.36%) told that moral duty was an important motivating factor to donate blood and 159 (31.86%) told that the possible incentives for voluntary blood donation is blood donor certificate. The present study revealed that, 304 (76.00%) were willing to donate blood, 54 (13.50%) had needed a blood transfusion in the past, 383 (95.75%) would accept blood transfusion if need arises, 159 (39.75%) would prefer to know the donor and 47 (11.75%) would like to receive blood from their relatives only. Among the 400 study participants, 76 (19.00%) had donated blood. Out of 76 donors, 62 (81.58%) had donated blood once and 30 (39.47%) were voluntary blood donation. Overall the knowledge, attitude and practice regarding blood donation was better in younger age group, male sex and literate participants. Conclusion: Knowledge and attitude regarding blood donation was good, but the practice was poor in our study. Overall the knowledge, attitude and practice were better among the participants who belonged to younger age group, male sex and literates. Key Words: blood donation, knowledge, attitude, practices, blood safety